The Consistency of Local Elites in the Stages of the Expansion of Central Luwu Regency into a New Autonomous Region - Muh Shafi'i Shahrir (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
The expansion of Central Luwu Regency is an effort of the Luwu community, especially the local elites of Luwu Regency as a representative, the Walenrang-Lamasi area as a candidate for a new autonomous region is geographically separated from its parent district, the idea of dividing Central Luwu Regency began in 2005 when the division of two sub-districts into six sub-districts in the Malenrang-lamasi region. This study aims to see how consistent local elites are in overseeing the expansion process and how the stages have been achieved. In writing this article, the method used is qualitative method, determination of selected informants with purposive techniques, data collection is carried out using interview techniques. The result of this research is that since the beginning of the entrenchment process, the local elites of Luwu Regency have several times formed a structured work agenda in accordance with the stages of expansion in the law, the process achieved is the fulfillment of administrative requirements, the acceptance of hearings in the DPR-RI and as an initiative in the plenary meeting to be forwarded to the president.